Optimization of trans-4-hydroxyproline synthesis pathway by rearrangement center carbon metabolism in Escherichia coli - Yu Gong; Ruiqi Wang; Ling Ma; Shuo Wang; Changgeng Li; Qingyang Xu (Microbial Cell Factories, 2023)
Abstract Background trans-4-Hydroxyproline (T-4-HYP) is a promising intermediate in the synthesis of antibiotic drugs. However, its industrial production remains challenging due to the low production efficiency of T-4-HYP. This study focused on designing the key nodes of anabolic pathway to enhance carbon flux and minimize carbon loss, thereby maximizing the production potential of microbial cell factories. Results First, a basic strain, HYP-1, was developed by releasing feedback inhibitors and expressing heterologous genes for the production of trans-4-hydroxyproline. Subsequently, the biosynthetic pathway was strengthened while branching pathways were disrupted, resulting in increased metabolic flow of α-ketoglutarate in the Tricarboxylic acid cycle. The introduction of the NOG (non-oxidative glycolysis) pathway rearranged the central carbon metabolism, redirecting glucose towards acetyl-CoA. Furthermore, the supply of NADPH was enhanced to improve the acid production capacity of the strain. Finally, the fermentation process of T-4-HYP was optimized using a continuous feeding method. The rate of sugar supplementation controlled the dissolved oxygen concentrations during fermentation, and Fe2+ was continuously fed to supplement the reduced iron for hydroxylation. These modifications ensured an effective supply of proline hydroxylase cofactors (O2 and Fe2+), enabling efficient production of T-4-HYP in the microbial cell factory system. The strain HYP-10 produced 89.4 g/L of T-4-HYP in a 5 L fermenter, with a total yield of 0.34 g/g, the highest values reported by microbial fermentation, the yield increased by 63.1% compared with the highest existing reported yield. Conclusion This study presents a strategy for establishing a microbial cell factory capable of producing T-4-HYP at high levels, making it suitable for large-scale industrial production. Additionally, this study provides valuable insights into regulating synthesis of other compounds with α-ketoglutaric acid as precursor.